2022
DOI: 10.1182/blood.2021014853
|View full text |Cite
|
Sign up to set email alerts
|

p57Kip2 regulates embryonic blood stem cells by controlling sympathoadrenal progenitor expansion

Abstract: Hematopoietic stem cells (HSCs) are of major clinical importance, and finding methods for their in vitro generation is a prime research focus. We demonstrate here that the cell cycle inhibitor p57Kip2/Cdkn1c limits the number of emerging HSCs by restricting the size of the sympathetic nervous system (SNS) and the amount of HSC-supportive catecholamines secreted by these cells. This regulation occurs at the SNS progenitor level and is in contrast to the cell-intrinsic function of p57Kip2 in maintaining adult HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…2B) (Fig. 2C and S3C) which are not captured in the Fadlullah et al (2022) and the Vink et al (2020) studies, but have been reported to sustain HSC specification (Fitch et al, 2012; Kapeni et al, 2022). Both these niche cell types are specifically present at 192h (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…2B) (Fig. 2C and S3C) which are not captured in the Fadlullah et al (2022) and the Vink et al (2020) studies, but have been reported to sustain HSC specification (Fitch et al, 2012; Kapeni et al, 2022). Both these niche cell types are specifically present at 192h (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Namely, we observed the successive specification of hemogenic endothelium (HE), and of pre-definitive erythro-myeloid progenitors (EMP), definitive myelo-lymphoid progenitors (MLP) and pre-HSC in coherent temporal progression, and we captured the formation of discrete micro-aggregates of hematopoietic cells in intimate association with endothelial-like lumina, reminiscent of mid-gestation HSC-generating aortic clusters. Hemato-endothelial development was accompanied by generation of stromal components critical for HSC emergence, including PDGFRA + mesenchyme (Chandrakanthan et al, 2022) and sympathetic neurons (Fitch et al, 2012; Kapeni et al, 2022), suggesting coordinated organisation of elements of a hemogenic niche. Importantly, the in vitro gastruloid system responded to a relevant oncogenic event unique to infant AML (infAML) and putatively characteristic of the developmental period, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Interestingly, other regulators, such as Dlk1 and p57Kip2, have also been reported to negatively regulate HSPC generation in a non-cell-autonomous manner. [22,23] Nevertheless, the molecular events and mechanisms restraining EHT are poorly understood.…”
Section: Introductionmentioning
confidence: 99%